Occurrence and Determinants of Postpartum Maternal Morbidities and Disabilities among Women in Matlab, Bangladesh (Journal of Health, Population and Nutrition, 2012)
The burden of maternal ill-health includes not only the levels of maternal mortality and complications during pregnancy and around the time of delivery but also extends to the standard postpartum period of 42 days with consequences of obstetric complications and poor management at delivery. There is a dearth of reliable data on these postpartum maternal morbidities and disabilities in developing countries, and more research is warranted to investigate these and further strengthen the existing safe motherhood programmes to respond to these conditions. This study aims at identifying the consequences of pregnancy and delivery in the postpartum period, their association with acute obstetric complications, the sociodemographic characteristics of women, mode and place of delivery, nutritional status of the mother, and outcomes of birth. From among women who delivered between 2007 and 2008 in the icddr,b service area in Matlab, we prospectively recruited all women identified with complicated births (n=295); a perinatal mortality (n=182); and caesarean-section delivery without any maternal indication (n=147). A random sample of 538 women with uncomplicated births, who delivered at home or in a facility, was taken as the control. All subjects were clinically examined at 6-9 weeks for postpartum morbidities and disabilities. Postpartum women who had suffered obstetric complications during birth and delivered in a hospital were more likely to suffer from hypertension [adjusted odds ratio (AOR)=3.44; 95% confidence interval (CI)=1.14-10.36], haemorrhoids (AOR=1.73; 95% CI=1.11-3.09), and moderate to severe anaemia (AOR=7.11; 95% CI=2.03- 4.88) than women with uncomplicated normal deliveries. Yet, women who had complicated births were less likely to have perineal tears (AOR=0.05; 95% CI=0.02-0.14) and genital prolapse (AOR=0.22; 95% CI=0.06-0.76) than those with uncomplicated normal deliveries. Genital infections were more common amongst women experiencing a perinatal death than those with uncomplicated normal births (AOR=1.92; 95% CI=1.18-3.14). Perineal tears were significantly higher (AOR=3.53; 95% CI=2.32-5.37) among those who had delivery at home than those giving birth in a hospital. Any woman may suffer a postpartum morbidity or disability. The increased likelihood of having hypertension, haemorrhoids, or anaemia among women with obstetric complications at birth needs specific intervention. A higher quality of maternal healthcare services generally might alleviate the suffering from perineal tears and prolapse amongst those with a normal uncomplicated delivery.   DOI: http://dx.doi.org/10.3329/jhpn.v30i2.11308   J HEALTH POPUL NUTR 2012 Jun;30(2):143-158